What Type of Body Shape Moves Children? An Experimental Exploration of the Impact of Narrative Cartoon Character Body Shape on Children’s Narrative Engagement, Wishful Identification, and Exercise Motivation - Alon, Dar; Sousa, Caio Victor; Lu, Amy Shirong (Frontiers in Psychology, 2021)
Background: The incorporation of narratives helps to enhance children’s engagement in Active Video Games (AVGs), thus increasing moderate-to-vigorous physical activity (MVPA). Specific narrative elements, such as the visual representation of the characters’ body shape, have been rarely manipulated to explore their role in modulating children’s narrative engagement and exercise motivation. Objective: To investigate the effects of character body shape manipulation (overweight/obese, average, or athletic slim) on children’s narrative immersion, narrative engagement, wishful identification, as well as their mediating effect on AVG and PA motivation. Methods: Children ages 8 -12 years old (N=87) were randomly assigned to watch a 15-minute animated video (designed for an existing AVG) in which the main characters had an overweight/obese, or average*, or athletic slim body shape (all other elements were identical). Children’s narrative immersion, narrative engagement, wishful identification, and AVG and physical activity motivation were then assessed. Results: Controlling for social desirability, the analysis indicated that participants with a BMI of greater than the 75th percentile had a significantly higher narrative immersion, narrative engagement, wishful identification, and physical activity motivation when video characters were set to the overweight/obese condition, than they did for video characters set to the average or athletic slim conditions. On the other hand, children of equal or less than the 75th percentile exposed to the average character body condition had a greater narrative engagement, wishful identification, and physical activity motivation than overweight/obese or athletic slim conditions. A mediation analysis with structural equation modeling indicated that narrative engagement mediated the effect between character body shape and AVG and physical activity motivation. Conclusions: Narrative cartoon characters that mirror the target participant’s body shape can increase narrative engagement, which in turn mediates AVG and physical activity motivation. Content producers should identify optimal strategies in character body shape design to encourage children of different weight status to participate in PA with engaging stories to maximize health narratives’ persuasive potentials.